TRENDS AND PERSPECTIVES ON ENTREPRENEURIAL EDUCATION IN ROMANIA AND THE EU - Casiana ILLE (Annals of the University of Oradea: Economic Science, 2021)
Entrepreneurial education (EE) has been a blossoming subject over the past years especially due to its importance and relevance to the economy both regionally and globally. The academic world still needs to conduct sustained research on the topic in order to fully throw a light on the importance that EE has on the society and its decisive role in transforming it. Economic, financial and EE has gained new dimensions lately, with an important raise of the focus both in theory and practice. This research studies the need for EE and financial literacy. In Europe, recent surveys show that young people acknowledge their lack of knowledge regarding entrepreneurship and state that schools should help them have an entrepreneurial mindset and know more about finances. In today’s dynamic environment and especially after the covid-19 crisis, the need on the workplace has changed and the skills that can be acquired through entrepreneurship and financial training and acknowledged by scholars, population, businesspeople and media as vital for the way things work in today’s economy. Teaching individuals how to think entrepreneurial becomes even more important in times of crises, or in a dynamic environment, where creativity, adaptability and innovation are key for survival. Key trends and developments are analyzed and the actors involved in shaping and raising awareness regarding financial illiteracy and the need for EE.